Penerapan Asesmen Kurikulum Merdeka pada Pembelajaran Ilmu Pengetahuan Sosial di Kelas VII SMP Adz-Dzikir Jember Tahun Ajaran 2024-2025 - Eka Fitriany; M.Ikbal Ibrahim H; Ilfiana Firzaq Arifin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the implementation of the Independent Curriculum assessment in Social Studies (IPS) learning in seventh grade students at Adz-Dzikir Junior High School, Jember, in the 2024–2025 academic year. The Independent Curriculum emphasizes assessment as an integral part of the learning process to encourage holistic student competency achievement. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that teachers have implemented various assessments, including diagnostic, formative, and summative assessments. Assessments are conducted not only to measure learning outcomes but also to understand student needs and development. Obstacles in implementing assessments include teachers' limited understanding of the principles of the Independent Curriculum and a lack of supporting facilities. However, the implementation of this assessment has a positive impact on increasing student engagement and motivation. These findings indicate that assessments in the Independent Curriculum have the potential to improve the quality of Social Studies learning if implemented consistently and supported by adequate teacher training.